Strategi Gerilya Raden Intan II dalam Perang Melawan Belanda di Lampung 1850-1856 - Rohmatillah, Itsna (Historia Madania: Jurnal Ilmu Sejarah, 2025)
This research analyzes the resistance strategies of Raden Intan II against the Dutch during the period of 1850-1856 using historical research methods. The findings indicate that Raden Intan's resistance was driven by his ancestral belief regarding the Dutch as enemies to be fought, as well as his role as the leader of Kahuripan. This resistance was carried out through guerrilla tactics in response to the Dutch's superiority in weaponry. However, the success of this strategy was halted when Raden Ngarapat betrayed, revealing Raden Intan II's whereabouts, resulting in his death. The impact was felt by both parties; the Lampung community lost their resistance leader and suffered material losses, while the Dutch also lost personnel and assets due to the six-year-long resistance, requiring significant war funds.